The Effect of Accounting Information Systems, Influencer Marketing, E-Commerce, and Financial Technology on the Performance of MSMEs in Surakarta City - Putri Dewi Langit; Fuad Hudaya Fatchan (Majapahit Journal of Islamic Finance and Management, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a strategic sector that plays a crucial role in driving economic growth and equitable income distribution. Amidst the development of digital technology, MSMEs are required to adopt various technological innovations to improve their business performance. This study aims to analyze the influence of Accounting Information Systems, Influencer Marketing, E-Commerce, and Financial Technology on the performance of MSMEs in Surakarta City. This study used a quantitative approach with a survey method. The sample consisted of 100 MSMEs in the Food and Beverages (FnB) sector selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that E-Commerce and Financial Technology have a positive and significant impact on MSME performance, while Accounting Information Systems and Influencer Marketing have no significant impact on MSME performance. These findings indicate that the use of digital sales platforms and financial technology plays a greater role in improving MSME performance than the use of accounting information systems and influencer-based marketing strategies. This research is expected to provide consideration for MSMEs and local governments in formulating digital technology-based MSME development policies.